Discontinuation of oral anticoagulation preceding acute ischemic stroke – prevalence and outcomes: Comprehensive chart review. Issue 8 (6th November 2015) - Vanga, Subba R; Satti, Sudhakar R; Williams, James; Weintraub, William; Doorey, Andrew
Abstract: Introduction: Oral anticoagulants (OAC) are the therapy of choice to prevent thromboembolism in patients at risk. Discontinuation of OAC prior to elective medical and surgical procedures may reduce the risk of bleeding, but may expose patients to increased risk of thromboembolism and ischemic stroke. The current public health burden of ischemic strokes associated with OAC discontinuation is unknown. We aimed to study the prevalence OAC discontinuation in patients who presented with acute ischemic stroke as well as the outcomes of these strokes. Methods: Retrospective cross-sectional study by intensive chart review of all acute ischemic stroke patients over 6 months in a large tertiary care community hospital. Results: A total of 431 patients with acute ischemic stroke were admitted during study period, of which 11 (2.6%) had OAC discontinuation within 120 days prior to the index admission. Several strokes occurred after relatively brief discontinuations. The patient group with discontinuation was older, had higher comorbidities and also had a clinically significant stroke and resulting higher mortality and morbidity. Conclusion: About 2.6% or 1 in every 38 of all ischemic stokes occurred after OAC discontinuation. Strokes occurring after OAC discontinuation also have higher mortality and morbidity. Our data suggest that any planned discontinuation of OAC, however brief, should be carefully considered.